Reporting on capacity-building and technology support under the Paris Agreement Issues and options for guidance - Garrett, Justine (OECD Publishing, 2018)
The enhanced transparency framework for climate action and support envisaged by the Paris Agreement is to "build on and enhance" current transparency arrangements under the United Nations Framework Convention on Climate Change (UNFCCC). This paper draws lessons from current reporting by Annex I and non-Annex I countries both within and outside the UNFCCC reporting framework to provide options that might inform the development of modalities, procedures and guidelines (MPGs) for reporting of technology transfer and capacity-building support under the Paris Agreement. The paper offers six options for consideration by Parties, with an emphasis on reporting by developing country Parties, given that very limited guidance has been available to these Parties to date. The options include how Parties might provide more guidance for reporting separately on financial, technology and capacity-building support; frame reporting of support needs and support received in the context of nationally determined contributions (NDCs); and facilitate more consistent use of key terminology and clearer reporting
Keywords: Environment